2016
DOI: 10.1016/j.jagp.2016.01.134
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea is Linked to Depression and Cognitive Impairment: Evidence and Potential Mechanisms

Abstract: Obstructive sleep apnea (OSA) is highly prevalent but very frequently undiagnosed. OSA is an independent risk factor for depression and cognitive impairment/dementia. Herein the authors review studies in the literature pertinent to the effects of OSA on the cerebral microvascular and neurovascular systems and present a model to describe the key pathophysiologic mechanisms that may underlie the associations, including hypoperfusion, endothelial dysfunction, and neuroinflammation. Intermittent hypoxia plays a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
4
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(137 citation statements)
references
References 118 publications
4
119
4
10
Order By: Relevance
“…The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40). Several studies have shown that existence of treatment resistant symptoms in patients with OSA might be due to depression and not due to OSA per se (41)(42)(43).…”
Section: Discussionsupporting
confidence: 90%
“…The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40). Several studies have shown that existence of treatment resistant symptoms in patients with OSA might be due to depression and not due to OSA per se (41)(42)(43).…”
Section: Discussionsupporting
confidence: 90%
“…These alterations caused cognitive impairments in many domains, such as attention, memory, executive function, psychomotor function and visuospatial function [53], which can lead to mild cognitive impairment (MCI) and dementia in the aging population [58].…”
Section: Obstructive Sleep Apnea Syndromementioning
confidence: 99%
“…sometimes including cognitive impairment), explore heterogenous populations and stipulate various mechanisms by which recurrent obstructive episodes might cause changes in mental status . Although postoperative delirium may be reflective of a neuro‐inflammatory process that is caused by catabolic surgical insults, it shares some of the pathophysiology thought to underlie endothelial and vasomotor changes in the brain of patients with OSA that may result from hypoxia and changes in perfusion due to the effects of repeated airway obstructions on cardiovascular function .…”
Section: The Outcomes Of Pain and Deliriummentioning
confidence: 99%